Making the Technological Transition – Citizens' Encounters with Digital Pension Services. (14th August 2014) - Breit, Eric; Salomon, Robert
Abstract We examine in this article the impact of digitization on the provision of public services by studying how citizens experience the use of web portals in their pension planning. Based on focus groups and user test material, we elucidate five critical phases that each operate as an obstacle for citizens' further engagement in the digital self‐service process: interest, access, comprehension, reflection and support. We argue that these phases and the obstacles they entail illustrate a transition away from a situation in which control and agency over the quality of public services is embedded in a dyadic relationship between citizens and frontline personnel, and to a situation characterized by more complex relations between citizens, the front line, and the digital infrastructure. We argue that this transition implies that citizens are required to possess a new type of competence that contains both financial and digital skills. Citizens who are unable to develop or acquire such competence are likely to be disadvantaged by the services. Lastly, we argue that these developments pose significant challenges for public administrations to ensure the overall quality of the public services.